Evaluating the Effectiveness of Surface Water Tax Collection Mechanisms: A Case Study of the Samsat Office in Gowa Regency - Muhammad Khaedar Sahib; Masrullah; Andi Nur Halisa (Jurnal Riset Perpajakan: Amnesty, 2026)
This study examines the effectiveness of surface water tax collection mechanisms implemented by the Samsat Office of Gowa Regency, Indonesia, in the context of increasing regional revenue demands and the need for efficient public financial administration. Despite the significant potential of surface water taxation as a source of locally generated revenue, its realization has shown inconsistent patterns, particularly the recurring accumulation of payments near the end of the fiscal year. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving tax officers, local government representatives, and key taxpayers. The analysis reveals several key findings. First, administrative procedures for tax assessment and billing are generally well structured; however, operational implementation remains constrained by limited human resources, inadequate digital integration, and dependence on manual verification. Second, the concentration of payments in December is influenced by taxpayer behavior, corporate cash flow cycles, and external audit requirements, indicating structural weaknesses in periodic monitoring. Third, the tax revenue structure is highly dependent on a small group of major taxpayers, posing fiscal vulnerability for the region. Overall, while the tax collection mechanism meets regulatory requirements, its effectiveness is hindered by technical, behavioral, and institutional factors. The study recommends strengthening digital reporting systems, implementing periodic compliance reminders, enhancing inter-agency coordination, and diversifying the taxpayer base to ensure sustainable regional revenue.